The Diversification of Products for Empowerment Women’s Keliling Benteng Ulu Village, Martapura Barat Subdistrict, Banjar District - Isnaini; Asnawati; Yuliani, Rahma; Riyani, Risma Yulfa; ‘Ibaadurrahmaan, Khansa Khafiya; Ariady, Nabilla Azzahra (Jurnal Pengabdian Masyarakat Formosa, 2024)
In 2023, the PKK women's group in Keliling Benteng Ulu Village, West Martapura District, Banjar Regency has started producing instant herbal drinks with the herbal name "Wiras".  For almost 1 year now, only one type of product has been made.  It is necessary to diversify the products produced.  The aim of this activity is to provide training in making instant drinks made from ginger and tomatoes.  In this community service activity, training on instant ginger and tomato drinks will be carried out.  As an evaluation, participants will be asked to independently make instant ginger and tomato drinks and send a video when making them. As a result of this activity, training has been carried out in making instant drinks in the form of instant ginger and instant tomatoes.  The instant ginger drink made is called JaRi (original ginger) while the instant tomato drink is called MST (Minuman Sari Tomat).